Deficiência aguda de tiamina: Efeitos no crescimento e resposta quimioterápica de um fibro-histiocitoma maligno de rato - Schor, Paulo (2023)
The present investigation has been carried on to study the effects of acute thiamine deficiency on the growth and response to chemotherapy of a malignant fibrohistiocytoma (MFH). Rats were inoculated subcutaneously with a tumoral cell suspension and divided into four groups of 10 animals each: animals fed with a thiamine-free diet (TFD); animals fed with a thiamine-free diet and treated with vincristine sulfate (TFV); animais fed a with control diet (CD); and animais fed with a control diet and treated with vincrístine sulfate (TFD). The animals treated with vincristine sulfate (TFV and CDV) showed a decrease in tumoral volume when compared to untreated animais (TFD and CD). The thiamine-deficient and the treated rats (TFV) showed no difference in tumoral volume when compared to animais receiving control diet and treated withvincristine sulfate (TFD). These data led us to conclude that acute thiamine deficiency per se does not alter MFH growth and does not modify the response of the tumor to chemotherapy with vincristine sulfate.